Activities of city public administration in regulation of economy, construction and urban land improvement (Russian experience). Issue 1 (March 2020) - Zolotareva, M V
Abstract: The paper addresses activities of City Duma authorities under new conditions of restructuring the management of the urban economic and construction sector. In the course of those reforms, legislative materials serving as the basis for new principles of territorial, sectoral and local management were the most important at the time. The reforms of the second half of the 19 th century not only changed the state policy of control over civil engineering but also ensured partial delegation of responsibilities for the economic and construction sector as well as urban land improvement to the urban community. Besides that practical work, the government initiated legislative activities at City Dumas. Despite the fact that the Building Code remained the main legislative document, mandatory regulations of urban communities served as its subordinate acts taking into account local specifics.